Basic concepts of criminal law - Fletcher, George P. (Oxford University Press, 1998)
Criminal law, according to George Fletcher's sharp new book, has become localized law in the sense that each country and, within the US, each state has adopted its own set of criminal codes, conceptions of punishable behavior, and so on. Basic Concepts of Criminal Law maintains that there is a much greater degree of unity among diverse systems of criminal justice than commonly realized, and that any adequate system of criminal law must necessarily address a set of universal, basic issues. Fletcher introduces and explains in detail twelve concepts that both shape and guide every system of criminal justice in the world. Knowledge of these ideas is essential to understanding not only the general structure of the law but also its local and national variations. This fundamental study will enlighten and challenge neophytes and experts alike.